Urban and Visual Culture in Contemporary Iran Non-Visibility and the Politics of Everyday Presence - Dibazar, Pedram (Bloomsbury Publishing USA, 2021)
Cover -- Contents -- List of Illustrations -- Acknowledgements -- Introduction -- 1 Streets -- Capturing the non-visibility of everyday presence -- Urban emptiness -- Absent presence -- An orientation towards the everyday -- 2 Cars -- Inhabiting the everyday, enacting an embodied cinema of mobility -- On the move: Abbas Kiarostami's wandering cars and extended presence -- Dwelling in mobility -- Mobilizing the look -- An embodied cinema of everyday interaction -- Conclusion -- 3 Rooftops -- The invisibility and ambiguity of leftover space -- Rooftops and the everyday city -- Rooftops of Iran: Memoirs and popular culture -- On leftover space -- Urban rooftops in Iran: The ambivalence of leftover space -- Rooftop protests: The everyday practice of shouting from rooftops -- Conclusion -- 4 Shopping centres -- The ambivalence of the scopic regime of the stroll -- Ambiguities of the shopping centre -- The scopic regimes of shopping -- Going for a walk in the shopping centre -- Conclusion -- 5 Sports -- The unrelenting visibility of wayward bodies -- Sports and everyday life in Iran: A short history -- Geographies and visualities of sport -- The hypervisibility of television sports -- The spectral community of television sports spectators -- Conclusion -- Conclusion -- Bibliography -- Index.